Accessible Stories within Mediascapes: Voicing Otherness in Digital Museums - Greco, Gian Maria; Rizzo, Alessandra; Spinzi, Cinzia (Journal of Audiovisual Translation, 2022)
This article presents the first steps in the investigation of the potential for digital storytelling and digital museums to be used as instruments for access, as enablers of epistemic and poietic agency. Digital storytelling and migration museums are used as a case study to explore in what ways digital storytelling impacts meaning-making processes performed by migrants, allowing them to become active creators and disseminators of their own experiences. Through the combination of corpus linguistics, systemic functional linguistics, and lexical semantic analysis, an ad-hoc comparable corpus of migrant narratives in English and in Italian was cross-examined in order to scrutinise the conceptual categories activated in these stories. The mixed-methods analysis led to the identification of the most common lexico-semantic features forming the knowledge frames of the experiential world of migrants. Results show that each national narrative makes use of its own grammar and lexico-semantic domains, a set of semantic and syntactic patterns associated with the production of stories of migration within the context of transmedia textual subtypes. These domains are strategic, as they give access to marginalised stories within digital museum settings. Lay summary Adopting the perspective of accessibility studies, digital storytelling is interpreted as a series of instruments for access, as an enabler of epistemic and poietic agency. That is, digital storytelling empowers people to express their voice and become active creators and disseminators of their own experiences. In order to investigate the potential of digital storytelling as a tool for access, we created a comparable corpus made of migrant narratives in English and in Italian spread across museum platforms. Then we cross-examined the corpus through a combination of quantitative and qualitative methodologies in order to examine the conceptual categories activated in these stories. More specifically, we analysed and identified which linguistic strategies have been employed by the storytellers to inform the audience, what knowledge frames have been adopted to tell their experiences and expectations, and what similarities or differences exist among stories told by migrants who have settled down in different parts of the world. Showing that each national narrative makes use of its own semantic and syntactic patterns, our results support the idea of digital storytelling as an access enabler and digital museums as novel environments which jointly empower people with the tools and conditions to take a proactive role.